IMPLEMENTASI KEBIJAKAN DESA BUDAYA DALAM UPAYA PELESTARIAN BUDAYA LOKAL - Reny Triwardani; Christina Rochayanti (Universitas Tribhuwana Tunggadewi, 2014)
The serious challenge faced of local culture is to preserve its existence in the midst of the stream of globalization. Accurate strategies need to be defined to strengthen its endurance as a social capital in recent society. Cultural village is a product of policy of Yogyakarta regional government which promote the potency of local culture based on local people empowerment as an effort to preserve local culture. This research intended to analyze the implementation of cultural village policy as an effort to preserve local culture in Yogyakarta regional. The approach was descriptive-qualitative with case study method on a cultural village in Banjarharjo, Kali Bawang, Kulon Progo. The findings of this research showed that on the stages of implementation cultural village policy as a model of local culture preservation need to be followed with the policy of cultural village governance so that would be able to increase the welfare of this local culture conservationist society.